Gut Bacterial Communities in Geographically Distant Populations of Farmed Sea Bream (Sparus aurata) and Sea Bass (Dicentrarchus labrax) - Eleni Nikouli; Alexandra Meziti; Efthimia Antonopoulou; Eleni Mente; Konstantinos A. Kormas (Microorganisms, 2018)
This study investigated the profile of the autochthonous gut bacterial communities in adult individuals of Sparus aurata and Dicentrarchus labrax reared in sea cages in five distantly located aquaculture farms in Greece and determine the impact of geographic location on them in order to detect the core gut microbiota of these commercially important fish species. Data analyses resulted in no significant geographic impact in the gut microbial communities within the two host species, while strong similarities between them were also present. Our survey revealed the existence of a core gut microbiota within and between the two host species independent of diet and geographic location consisting of the Delftia, Pseudomonas, Pelomonas, Propionibacterium, and Atopostipes genera.